Impaired Visual Working Memory Consolidation in Schizophrenia - Fuller, Rebecca L. (2009)
This study investigated working memory (WM) consolidation, that is, the time required to create durable WM representations, at different levels of WM load in schizophrenia. Twenty-three schizophrenia spectrum patients and 16 control subjects participated in a change-detection task in which a sample array of 1–3 squares appeared followed by a delay and a test array. An array of pattern masks was inserted into the delay interval—covering the locations of the sample-array squares—100–800 ms after the offset of the sample array. If a durable WM representation is formed prior to mask onset, the mask should not impair performance. The degree of masking at an interval reflects the degree of WM consolidation at that time. Neither group showed masking at set size 1. Unlike controls, patients demonstrated robust masking effects at set size 2. Both groups showed masking at set size 3, but masking effects were larger and longer lasting in patients. These data demonstrate abnormally prolonged WM consolidation in schizophrenia. This impairment may slow the formation of stable representations of the visual environment, impacting everyday visually guided behavior.